2021
DOI: 10.3748/wjg.v27.i40.6967
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting anxiety, depression, and self-care ability in patients who have undergone liver transplantation

Abstract: BACKGROUND Depression, anxiety, and altered self-care ability are among the most important factors affecting the quality of life of liver transplant recipients. Depending on the severity of the underlying liver disease, signs and symptoms of anxiety and depression may become more pronounced. AIM To evaluate the factors affecting depression, anxiety and self-care abilities of liver transplant recipients. METHODS Recipients who are ≥ 18 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…For these reasons, reduced postoperative quality of life and psychosocial disorders may be higher, especially in patients. Furthermore, the presence of HCC as an indication of LT has an additional impact on the patients’ psychosocial well-being and quality of life [ 41 ]. In addition, patients with impaired quality of life in the pre-LT period (such as advanced end-stage liver disease and complications of cirrhosis that deteriorate the physiologic condition of the patient) have also deteriorated the health-related quality of life in the post-LT period.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, reduced postoperative quality of life and psychosocial disorders may be higher, especially in patients. Furthermore, the presence of HCC as an indication of LT has an additional impact on the patients’ psychosocial well-being and quality of life [ 41 ]. In addition, patients with impaired quality of life in the pre-LT period (such as advanced end-stage liver disease and complications of cirrhosis that deteriorate the physiologic condition of the patient) have also deteriorated the health-related quality of life in the post-LT period.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no statistical significance in anxiety of patients with CP with different monthly income. It has been reported that monthly income was shown to have significant impacts on anxiety symptoms among stroke patients, 27 patients with liver transplantation, 28 and dialysis patients. 29 It is unclear why monthly income of patients with CP had no impact on anxiety symptoms in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed some of the known risk factors for depression in transplantation: low income [42], female gender, younger age [35] and unemployment [19]. Laboratory values associated with increased risk of depression in kidney recipients were parathyroid hormone level, ferritin levels [43] and triglyceride levels [25].…”
Section: Solid Organ Transplantationmentioning
confidence: 93%
“…Laboratory values associated with increased risk of depression in kidney recipients were parathyroid hormone level, ferritin levels [43] and triglyceride levels [25]. Other medical factors associated with depression include biliary complications and hepatocellular carcinoma for liver transplant recipients [42], New York Heart Associations class II, III/IV and steroid treatment for heart recipients [41], fat mass and anthropometric parameters of obesity for kidney recipients [25]. In liver transplant candidates, there were no differences in depression between patients with low MELD score (<15) and those with high MELD score (>15) [44].…”
Section: Solid Organ Transplantationmentioning
confidence: 99%